Mechanism of the Dual Activities of Human CYP17A1 and Binding to Anti-Prostate Cancer Drug Abiraterone Revealed by a Novel V366M Mutation Causing 17,20 Lyase Deficiency - Mónica Fernández-Cancio; Núria Camats; Christa E. Flück; Adam Zalewski; Bernhard Dick; Brigitte M. Frey; Raquel Monné; Núria Torán; Laura Audí; Amit V. Pandey (MDPI AG, 2018)
The CYP17A1 gene regulates sex steroid biosynthesis in humans through 17α-hydroxylase/17,20 lyase activities and is a target of anti-prostate cancer drug abiraterone. In a 46, XY patient with female external genitalia, together with a loss of function mutation S441P, we identified a novel missense mutation V366M at the catalytic center of CYP17A1 which preferentially impaired 17,20 lyase activity. Kinetic experiments with bacterially expressed proteins revealed that V366M mutant enzyme can bind and metabolize pregnenolone to 17OH-pregnenolone, but 17OH-pregnenolone binding and conversion to dehydroepiandrosterone (DHEA) was impaired, explaining the patient’s steroid profile. Abiraterone could not bind and inhibit the 17α-hydroxylase activity of the CYP17A1-V366M mutant. Molecular dynamics (MD) simulations showed that V366M creates a “one-way valve” and suggests a mechanism for dual activities of human CYP17A1 where, after the conversion of pregnenolone to 17OH-pregnenolone, the product exits the active site and re-enters for conversion to dehydroepiandrosterone. The V366M mutant also explained the effectiveness of the anti-prostate cancer drug abiraterone as a potent inhibitor of CYP17A1 by binding tightly at the active site in the WT enzyme. The V366M is the first human mutation to be described at the active site of CYP17A1 that causes isolated 17,20 lyase deficiency. Knowledge about the specificity of CYP17A1 activities is of importance for the development of treatments for polycystic ovary syndrome and inhibitors for prostate cancer therapy.